Comment on “On Gonorynchus, Gonorhynchus, Gonorinchus, Gonorhinchus, and Gonorrhynchus, and some other names of labeonine fishes (Teleostei: Gonorhynchidae and Cyprinidae)” by Kottelat (2016) - Ciccotto, Patrick J.; Page, Lawrence M. (Zootaxa, 2017)
Kottelat (2016) noted that ‘Gonorhynchus McClelland, 1838,’ the name used for a South Asian cyprinid genus recognized by Yang et al. (2012) and revised by Ciccotto & Page (2016), does not exist or is a junior homonym of Gonorhynchus Cuvier, 1816. He further noted that Tariqilabeo Mirza & Saboohi, 1990 is the valid genus name for the species recognized in Gonorhynchus by Yang et al. (2012) and by Ciccotto & Page (2016). Kottelat also rejected the placement of Epalzeorhynchus bicornis Wu, 1977 in this genus by Yang et al. (2012), instead placing it in the monotypic Akrokolioplax Zhang & Kottelat, 2006, and questioned the validity of the designation of the neotype of Cyprinus latius Hamilton, 1822 by Ciccotto & Page (2016). While we are in agreement with the validity of Tariqilabeo, we disagree with the use of Akrokolioplax and defend the designation of the neotype for C. latius.